1996
DOI: 10.1143/jjap.35.2520
|View full text |Cite
|
Sign up to set email alerts
|

Metalorganic Chemical Vapor Deposition of Complex Metal Oxide Thin Films by Liquid Source Chemical Vapor Deposition

Abstract: The implementation of ferroelectric thin films in advanced semiconductor devices is near; facile integration at ULSI geometries requires chemical vapor deposition (CVD) process technology. The low volatility and thermal stability of many of the existing source reagents has driven the development of liquid source CVD, in which composition is set by volumetric metering of liquids followed by flash vaporization. The methodology as well as early results for Ba1- x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Unlike in true ALD, the oxygen source (N 2 O or O 2 ) was passed through continuously, not pulsed, and the growth temperature was too high (620 C), considering the thermal stabilities of the precursors. For example, the titanium precursor, titanium tetraisopropoxide (Ti(O i Pr) 4 ), starts to decompose weakly above 250 C, [32] and completely destroys a surface-controlled growth at 350 C. [33] On the other hand, the b-diketonates do react with ozone, e.g., Sr(thd) 2 at around 300 C, but the resulting film is SrCO 3 or, when combined with titanium, an amorphous mixture, which needs to be annealed at 700 C to crystallize SrTiO 3 . [34] Recently we reported that the ALD of SrTiO 3 and BaTiO 3 thin films may be achieved at 250±325 C by using cyclopentadienyl compounds of strontium and barium, together with titanium tetraisopropoxide and water.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in true ALD, the oxygen source (N 2 O or O 2 ) was passed through continuously, not pulsed, and the growth temperature was too high (620 C), considering the thermal stabilities of the precursors. For example, the titanium precursor, titanium tetraisopropoxide (Ti(O i Pr) 4 ), starts to decompose weakly above 250 C, [32] and completely destroys a surface-controlled growth at 350 C. [33] On the other hand, the b-diketonates do react with ozone, e.g., Sr(thd) 2 at around 300 C, but the resulting film is SrCO 3 or, when combined with titanium, an amorphous mixture, which needs to be annealed at 700 C to crystallize SrTiO 3 . [34] Recently we reported that the ALD of SrTiO 3 and BaTiO 3 thin films may be achieved at 250±325 C by using cyclopentadienyl compounds of strontium and barium, together with titanium tetraisopropoxide and water.…”
Section: Introductionmentioning
confidence: 99%
“…[2±4] MOCVD is an attractive technique for the deposition of these materials, offering the potential for large area growth, good film uniformity, and excellent conformal step coverage at device dimensions less than 2 lm, but the processing of multi-component oxides using conventional gas delivery methods (bubbling a carrier gas through low volatility precursors held at high temperature) has proved difficult, with severe problems of compositional control due to precursor decomposition, and very low growth rates. This has led to the increased use of liquid injection MOCVD, [5,6] in which a precursor solution is injected directly into a heated evaporator and then transported by carrier gas into the reaction zone. This avoids precursor decomposition, as the precursors remain at room temperature up to the moment of injection, but there are the added requirements that the precursors must be soluble and stable in a suitable solvent and must not react with any co-precursors in solution.…”
Section: Introductionmentioning
confidence: 99%
“…As in complex 1, one of the phenyl groups is nearly co-planar with the b-diketonate ring (angle between C(10)±C (15) and O(5)±C(9)±C(16)±C(17)±O(6) plane = 9.52 (19)), whereas the other phenyl group is twisted out of the b-diketonate plane by an angle of 24.80 (19).…”
Section: Crystal Structures Of 1 Andmentioning
confidence: 99%
“…[22] A very small dihedral angle of 3.93(56) between C(2)± C(7) and O(1)±C(1)±C(8)±C(9)±O(2) shows that one phenyl ring is very close to being in the plane of the b-diketonate ring. The other phenyl ring is twisted somewhat out of this plane, presumably due to crystal packing constraints, as is shown by the larger dihedral angle of 20.13(43) between C(10)±C (15) and O(1)±C(1)±C(8)±C(9)±O(2). However, in solution, free from crystal packing effects, it is likely that both phenyl rings assume a co-planar configuration with the b-diketonate ring, allowing delocalization of the negative charge on the b-diketonate ring into the p-electron system of the phenyl rings, leading to resonance stabilization of the [dbm] group (see Sec.…”
Section: Crystal Structures Of 1 Andmentioning
confidence: 99%